Travestilidades: trajetórias de vidas, lutas e resistências como construção de sociabilidade - Navas, Kleber de Mascarenhas (2011)
This dissertation aims at a rapprochement with the life experiences of transvestites, so localized and situational, in order to contribute to the problems and expand the field of Social Work at the intersection with issues of human rights, gender, gender identity, and sexuality, among others. The first chapter seeks to pervade the thinking about the categories sexuality, gender and sexual diversity, highlighting the challenges and achievements of the LGBT movement today, and how social work fits in this fight. In Chapter 2 presents a survey of three subject, using the methodology of oral history, addressing issues relating to aspects of everyday life, taking into consideration their construction of the subject in relation to the varying practices of prejudice and rights violations. The confrontation of daily life, as well as the multiple forms of violence, by the resistance, poses a question and a challenge of how to mobilize individuals to face the difficulties in this way, and not suffering